2017
DOI: 10.1016/j.eurpolymj.2017.03.041
|View full text |Cite
|
Sign up to set email alerts
|

Natural antioxidants as melt stabilizers for PE: Comparison of silymarin and quercetin

Abstract: The stabilization effect of two flavonoid type natural antioxidants, silymarin (Si) and quercetin (Q), was compared in polyethylene (PE). Additive concentrations changed between 0 and 500 ppm in several steps and 1000 ppm Sandostab PEPQ phosphorus containing secondary stabilizer was also added to each compound. Stabilization efficiency was determined by changes in functional group (vinyl, residual PEPQ) content, melt flow rate (MFR), oxygen induction time (OIT), color and the consumption of the secondary antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…The goal was to study the dispersion and controlled release effect and not the development of an industrial package. All our studies on natural antioxidants showed that flavonoids usually are much more efficient than traditional phenolic antioxidants currently used in industrial practice [17][18][19][20].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The goal was to study the dispersion and controlled release effect and not the development of an industrial package. All our studies on natural antioxidants showed that flavonoids usually are much more efficient than traditional phenolic antioxidants currently used in industrial practice [17][18][19][20].…”
Section: Introductionmentioning
confidence: 91%
“…The antioxidant effect of curcumin [17], quercetin [18] and dihydromyricetin [19] was studied in a Phillips type polyethylene in the presence of a phosphorous secondary stabilizer and the stabilization efficiency of all three exceeded considerably that of the synthetic phenolic antioxidant routinely used in large quantity in industrial practice. The efficiency of another natural antioxidant, silymarin, a flavonolignan compound with the same basic structure as quercetin proved to be much less efficient [20].…”
Section: Introductionmentioning
confidence: 99%
“…A series of research results suggested that the effects of natural antioxidants in stabilizing of polyolefin come from the interaction of natural antioxidant and secondary antioxidant. [12,15,16,18] Thus, the interaction between puerarin and PEPQ was discussed in this section. For comparison, PE or PP modified with only PEPQ (PE-P 0 -P and PP-P 0 -P samlpes) and PE or PP modified with only puerarin (PE-P 1200 and PP-P 1200 samlpes) were prepared.…”
Section: Interaction Of Puerarin and Pepqmentioning
confidence: 99%
“…Quite a few of natural compounds derived from plants have been used as stabilizer for foods [3][4]5,6] and polymer. [7][8][9][10][11][12][13][14][15][16][17][18][19] Lignin that comes from cell walls of woods and grasses is a natural macromolecule polyphenol. PE mixed with a mass of lignin exhibited preferable thermooxidative stability and processing stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation